2019
DOI: 10.1002/chem.201902651
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of (Pentafluorosulfanyl)benzenes by Direct Fluorination of Diaryldisulfides: Synthetic Approach and Mechanistic Aspects

Abstract: Direct fluorination of ortho-, meta-a nd para-substituteda romatic thiols and disulfides using elemental fluorine afforded substituted (pentafluorosulfanyl)benzenes. This work thus represents the first study of the scope and limitation of direct fluorination for the synthesis of new SF 5 -containing building blocks. Fluorinationsi nb atch and flow modes were compared.Acomprehensive computational study was carried out employingd ensity functional and wave functionm ethods to elucidate the reaction mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
0
13
0
5
Order By: Relevance
“…Consequently, we avoided the isolation of larger quantities of [NEt Trifluoromethyl and pentafluorosulfanyl derivatives have a growing importance in pharmaceutical-and agrochemistry. [23,24,25] Recently, Togni and co-workers reported on a non-gaseous reagent to access aryl tetrafluorido-l 6 -sulfanyl chlorides (Ar-SF 4 Cl), a key intermediate for the synthesis of pentafluorosulfanyl aryls (Ar-SF 5 ). [24] Beier and co-workers recently studied the direct fluorination with dilute elemental fluorine and disulfides to directly obtain pentafluorosulfanyl aryls, a process with industrial application.…”
mentioning
confidence: 99%
“…Consequently, we avoided the isolation of larger quantities of [NEt Trifluoromethyl and pentafluorosulfanyl derivatives have a growing importance in pharmaceutical-and agrochemistry. [23,24,25] Recently, Togni and co-workers reported on a non-gaseous reagent to access aryl tetrafluorido-l 6 -sulfanyl chlorides (Ar-SF 4 Cl), a key intermediate for the synthesis of pentafluorosulfanyl aryls (Ar-SF 5 ). [24] Beier and co-workers recently studied the direct fluorination with dilute elemental fluorine and disulfides to directly obtain pentafluorosulfanyl aryls, a process with industrial application.…”
mentioning
confidence: 99%
“…Scheme 18 SF5-Arylation and heteroarylation of SF4Cl compounds via AgBF4 Cl-F exchange and reaction scope 20 Beier et al reported the direct fluorination of ortho-, meta-and para-substituted aromatic thiols and disulfides using elemental fluorine -reactions were performed in acetonitrile with 10 % F2/N2 mixture at -5 °C (optimised conditions) -which afforded the corresponding substituted SF5-benzenes (Scheme 19). 21 The main limitation of the method is represented by the competitive fluorination of the aromatic ring, so that only electron-deficient aryl sulfides/disulfides efficiently lead to the formation of the desired SF5-aromatics. Probably the main selling point of this method is the possibility of successfully reacting orthosubstituted aromatics, even with rather bulky groups, which are poorly reactive using other methods, and also synthesising bis-SF5-benzenes in one step.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In 2016 and 2019, Beier and co‐workers reported the direct fluorination of ortho ‐, meta ‐, and para ‐substituted aromatic thiols and disulfides using F 2 (Scheme 30). [73] By comparing the synthetic performance under batch and flow conditions, it was found that a hybrid batch‐flow process (synthesis of Ar−SF 3 in batch, then Ar−SF 5 in flow) provided good yields [73b] . By benchmarking experimental data with DFT calculations, the authors ruled out three nonradical pathways for the conversion of Ar−SF 3 into Ar−SF 5 .…”
Section: Fluorination Levelmentioning
confidence: 99%
“…[23b] In 2016 and 2019, Beier and co-workers reported the direct fluorination of ortho-, meta-, and para-substituted aromatic thiols and disulfides using F 2 (Scheme 30). [73] By Scheme 25. Pioneering syntheses of CÀ SF 5 and SF 5 Cl.…”
Section: Direct Oxidation Of Diaryldisulfides or Arylthiolsmentioning
confidence: 99%